Cold Exposure Induces Intestinal Barrier Damage and Endoplasmic Reticulum Stress in the Colon via the SIRT1/Nrf2 Signaling Pathway - Guo, Jingru; Hu, Huijie; Chen, Zhuo; Xu, Jing; Nie, Junshu; Lu, Jingjing; Ma, Li; Ji, Hong; Yuan, Jianbin; Xu, Bin (Frontiers in Physiology, 2022)
Ambient air temperature is a key factor affecting human health. Long-term exposure to a cold environment can cause various diseases, while the impact on the intestine, the organ which has the largest contact area with the external environment, cannot be ignored. In this study, we investigated the effect of chronic cold exposure on the colon and its preliminary mechanism of action. Mice were exposed to 4°C for 3 hours a day for 10 days. We found that cold exposure damaged the morphology and structure of the colon, destroyed the tight junctions of the colonic epithelial tissue, and promoted inflammation of the colon. At the same time, cold exposure also activated the unfolded protein response (UPR) in the colon and promoted apoptosis in intestinal epithelial cells. Chronic cold exposure induced oxidative stress in vivo, but also significantly enhanced the response of the Nrf2 pathway that promotes an anti-oxidant effect. Furthermore, we demonstrated that chronic cold exposure promoted p65 acetylation to aggravate the inflammatory response by inhibiting SIRT1. Similar results were observed following SIRT1 knock-down by shRNA in Caco-2 cells treated with Thapsigargin (Tg). Knock-down of SIRT1 promoted nuclear localization of Nrf2, and increased the level of Nrf2 acetylation. Taken together, our study indicates that cold exposure may aggravate endoplasmic reticulum stress and damage epithelial tight junctions in the colon by inhibiting SIRT1, which promotes nuclear localization of Nrf2 and induces an anti-oxidant response to maintain intestinal homeostasis. These findings suggest that SIRT1 is a potential target for regulating intestinal health under cold exposure conditions.